2016
DOI: 10.1007/82_2016_1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immunity Against Staphylococcus aureus

Abstract: A complex interplay between host and bacterial factors allows Staphylococcus aureus to occupy its niche as a human commensal and a major human pathogen. The role of neutrophils as a critical component of the innate immune response against S. aureus, particularly for control of systemic infection, has been established in both animal models and in humans with acquired and congenital neutrophil dysfunction. The role of the adaptive immune system is less clear. Although deficiencies in adaptive immunity do not res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 135 publications
(142 reference statements)
1
35
0
3
Order By: Relevance
“…With the advent of methicillin-resistant S. aureus and the threat of antibiotic resistance, developing a vaccine against S. aureus has become a priority. Humans do not generally develop robust protective immunity upon S. aureus infection, as indicated by the finding that individuals can be infected with S. aureus many times throughout life (Karauzum and Datta, 2016). Although there is evidence that protective immunity could be acquired, for example, in subjects colonized nasally with S. aureus , protection is generally modest (Wertheim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of methicillin-resistant S. aureus and the threat of antibiotic resistance, developing a vaccine against S. aureus has become a priority. Humans do not generally develop robust protective immunity upon S. aureus infection, as indicated by the finding that individuals can be infected with S. aureus many times throughout life (Karauzum and Datta, 2016). Although there is evidence that protective immunity could be acquired, for example, in subjects colonized nasally with S. aureus , protection is generally modest (Wertheim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, despite worldwide efforts, a vaccine for the clinically important Staphylococcus aureus has not made it to the market, yet. Basic research showed the importance of Th1 and Th17 responses in defence against staphylococci [68,69]. While Th17 is prominent in S. aureus clearance from skin and respiratory infections, Th1 responses protect from systemic infection.…”
Section: Multiple Causes May Prevent the Efficacy Of Bacterial Vacmentioning
confidence: 99%
“…It can infect almost all tissues and organs in humans, which leads to serious diseases such as endocarditis, pneumonia, and sepsis syndrome . Although the immune system evading mechanisms of S. aureus cause them to be highly pathogenic in humans, the bacteria can also promote immune activation . Staphylococcus aureus contains numerous types of toxins that induce the activation of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus contains numerous types of toxins that induce the activation of the immune system. Staphylococcal superantigens (SAgs), the potent immune stimulatory exotoxins, induce T‐cell activation and pro‐inflammatory cytokine production by directly cross‐linking MHC class II on DCs . It has been shown that the DCs are important in the presentation of staphylococcal enterotoxins on MHC class II and secrete interleukin‐12 (IL‐12) for the induction of T helper type 1 and cytotoxic T1 cells immune responses .…”
Section: Introductionmentioning
confidence: 99%